ENGLISH ENVIRONMENT PROGRAMS AT POLYTECHNIC OF NATIONAL INFORMATICS - Fiviyanti Hasim; Hamzah Machmoed; Nasmilah Nasmilah (JURNAL ILMU BUDAYA, 2018)
English Environment Programs is one of method In Improving Speaking Ability At Polytechnic of National Informatics. This research aims at finding out wheather or not the use of English environment Programs improve the speaking ability. This research used Quasy experimental method with two group pre-test and post-test design. The result of the data analysis showed that the degree of freedom (df) was 43 (n1 + n2 – 2) where n1 = 30 and n2 = 15 so 30 + 15 – 2 = 43), the level of significant (α) = 0.05, the t-test value of students’ speaking ability= 3.765, and the t-table value = 2.021. The t-test value is greater than the t-table value (3.765 > 2.021), this showed that there is a significant difference of improvement between the Control group and Experimental Group. It means that the Alternative Hypothesis (H1) is accepted while the Null Hypothesis (H0) rejected. Based on the result above, the researcher concluded that the using of English Environment Programs can improve the speaking ability of the second year students of Polytechnic of National Informatics